A novel monitoring method for gamma irradiation facility based on radio-voltaic and photovoltaic effects. (July 2021) - Bian, Mingxin; Tang, Xiaobin; Xu, Zhiheng; Hou, Zhenfeng; Yuan, Zicheng; Liu, Kai
Abstract: This paper presents a novel monitoring method for gamma irradiation facility, which has the advantages of big view, accurate and working in event of a power outage. The state of radioactive source is monitored based on the property of electrical signal curves from photovoltaic devices when they are facing the source frame, and these electrical signals are generated by radio-voltaic and photovoltaic effects. GaAs based photovoltaic device was selected as the module to convert the rays near the radioactive source into electrical signals by the two above effects, and a Co-60 facility for irradiation processing was used as monitored object in this work. The influence of parameters such as the distance between the Co-60 frame and the photovoltaic device array, better electrical signals for forming curves on the monitoring effect were analyzed by Geant4. And the monitoring effect of the Co-60 frame in many cases was studied by Geant4 and experiment. Simulation results show that there are optimal parameters to achieve best monitoring effect, and the distribution of the Co-60 rods on the frame, the working condition and integrity of the Co-60 frame can be clearly reflected with this method. The consistency of the tendency of the electrical signal curves in verification experiment and Geant4 simulation verified the feasibility of this monitoring method. This method may provide new ideas for monitoring system designed for irradiation facility, nuclear power plants and other scenarios with rays. Highlights: A radiation monitoring method based on "radio-voltaic/photovoltaic effects" was proposed and verified. The source frame was monitored based on the spatial distribution of rays. The lifting, damage and missing of the source frame can be monitored in real time and efficiently. The state of the radioactive source can be illustrated by the property of the electrical signal curves.